FAKTOR-FAKTOR YANG MEMICU JIWA KEWIRAUSAHAAN PADA PEDAGANG SARANA UPACARA HINDU DI DESA BITRA GIANYAR - dewa prabawa (Jurnal Ilmiah Manajemen & Bisnis, 2016)
Entrepreneurship can encourage or promote economic growth, and the future of society as well as for entrepreneurs. Thus, the fate of peoples and nations, is dependent upon individuals as the younger generation, to have a persistent entrepreneurial spirit, work diligently, and to be honest, creative, innovation and courage in trying, so as to produce goods or services. David McClelland argued that if a country wants to be prosperous, a minimum amount of 2% of the total population in the country to become entrepreneurs. The purpose of research: to identify and analyze the factors igniting the Spirit of Entrepreneurship and to determine the most dominant factor triggering the Spirit of Entrepreneurship in the village of Bitra Ginyar. The approach used was multiple linear regression approach. Samples taken were 32 respondents. The results expressed a positive influence of variable of personal factors (X1), environmental factors (X2) and sociological factors (X3) to trigger the entrepreneurial (Y). Based on the analysis of standardized coefficeents beta, sociological factors conferred the most dominant influence to the trigger of entrepreneurship in Bitra village of Gianyar.